INFLUENCE OF SOCIALIZATION ON ACADEMIC PERFORMANCE OF LEARNERS WITH HEARING IMPAIRMENT AT INCLUSIVE PRIMARY SCHOOLS IN KENYA: A CASE IN THAWABU PRIMARY OF NAIROBI CITY COUNTY - Owuor, Everlyne Achieng; Awori, Beatrice Bunyasi; Otieno, Syprine A. (African Journal of Education and Practice, 2020)
Purpose: This research aimed at determining the influence of socialization on performance of learners with hearing impairment at Thawabu Inclusive Public Primary School in Nairobi, Kenya. The objectives were to; establish modes of communication that promote socialization in an inclusive environment; establish strategies for boosting socialization to enhance academic performance; and establish challenges facing teachers in enhancing socialization to improve academic performance of learners with hearing impairment. Methodology: The research design was a case study design. Structured questionnaires and interviews were used to collect data. Purposive sampling was employed to select the school and learners with hearing impairment while hearing learners were randomly selected. Findings: The study found that: modes of communication among learners with hearing impairment, hearing learners and teachers create social and educational change for improvement of academic standards in the school and narrows the gap between those with hearing impairment and their hearing counterparts. Strategies like family support program (assisting children and families in language learning), family-infant-toddler program, and competent and consistent administration system promote learning. Socialization influences incidental learning of learners with hearing impairment to put them at par with their hearing peers on matters related to both academic performance and social advancement. Socialization makes learners with hearing impairment comfortable, self-esteemed, and self-actualized, hence improving educational performance. Unique contribution to theory, practice and policy: The study may help to promote attitudinal, psychological and educational change in all stakeholders for inclusive education to be a success and meaningful to learners with hearing impairment. The study recommends that the government should add specially qualified teachers of learners with hearing impairment in Thawabu among other inclusive public schools in Kenya to help promote socialization and to increase inclusivity of leaners with hearing impairment.